Prevalence, Treatment and Outcomes of Coexistent Pulmonary Hypertension and Interstitial Lung Disease in Systemic Sclerosis - Young, Amber (Arthritis Rheumatol, 2019)
OBJECTIVE: Systemic sclerosis (SSc) is associated with interstitial lung disease (ILD) and pulmonary hypertension (PH). We sought to determine prevalence, characteristics, treatment, and outcomes for subjects with PH in a SSc-associated ILD (SSc-ILD) cohort. METHODS: Subjects with SSc-ILD on high resolution computed tomography (HRCT) were included in a prospective observational cohort. Subjects had been screened for PH based on a standardized screening algorithm and underwent right heart catheterization (RHC), if indicated. PH classification was based on hemodynamics and extent of ILD on HRCT. Summary statistics and survival using Kaplan Meier method were calculated. RESULTS: Ninety-three subjects with SSc-ILD were included; 76% were female, 65.6% had diffuse SSc, mean age was 54.9 years, and mean SSc disease duration was 8 years. Twenty-nine subjects (31.2%) had RHC proven PH; of those 29 subjects, 24.1% had PAH, 55.2% had WHO Group III PH, 34.5% had WHO Group III PH with pulmonary vascular resistance > 3.0 Wood units, 48.3% had PH diagnosis within 7 years of SSc onset, 82.8% were treated with ILD therapy, and 82.8% were treated with PAH therapy. Survival rate at 3 years after SSc-ILD diagnosis for all subjects was 97%. Survival rate for those with SSc-ILD and PH at 3 years after PH diagnosis was 91%. CONCLUSION: In a large SSc-ILD cohort, a significant proportion of patients have coexisting PH, which often occurs early after diagnosis; most patients were treated with ILD and PAH therapies, and survival was good. Patients with SSc-ILD should be evaluated for coexisting PH.